DNA Conductivity: Triggering Mechanism for DNA Electrical Conductivity: Reversible Electron Transfer between DNA and Iron Oxide Nanoparticles (Adv. Funct. Mater. 12/2015). (March 2015) - Magro, Massimiliano; Baratella, Davide; Jakubec, Petr; Zoppellaro, Giorgio; Tucek, Jiri; Aparicio, Claudia; Venerando, Rina; Sartori, Geppo; Francescato, Federica; Mion, Fabio; Gabellini, Nadia; Zboril, Radek; et al.
Abstract : DNA based self‐assembled nanoconjugates and a macroscopic metamaterial are synthetized by R. Zboril, F. Vianello, and co‐workers on page 1822 using naked maghemite nanoparticles as electroactive supports. DNA nanoconjugates show reversible electrochemical behavior and better electrochemical performances with respect to bare nanoparticles. The intimate contact between DNA and nanoparticles is studied and electron transfer at the interface between nanoparticles and DNA is unequivocally demonstrated by Mössbauer spectroscopy and modeled by density functional theory.